Pre-service teachers' use of ChatGPT and acquired moral dissonance - Caling, James G.; Antonio, Joanna Kyla T.; Dimatatac, Ma Fe L.; Sabellano, Mitz D.; Vicencio, Victoria Dhane R.; Prias, Justin M.; Ramos, John Carlo M. (Journal of Interdisciplinary Studies in Education, 2025)
This study explores how 10 pre-service teachers at a teacher education institution in Manila utilize ChatGPT and experience moral dissonance. Data were gathered through semi-structured interviews, revealing that ChatGPT is employed for paraphrasing, information search, organizing ideas, and simplifying complex concepts. However, its use develops dependency, diminishes critical thinking, and creates tension between convenience and academic integrity. They justified their actions citing academic pressures, workload, and ineffective teaching practices. The findings highlight the moral acquired such as convenience versus conscience, pressure versus principle, and innovation versus integrity. These conflicts emphasizes the need for institutions to establish ethical guidelines and promote AI literacy. They also promote foster ethical practices among pre-service teachers and equip them to integrate AI responsibly into their practices. This study contributes to understanding the moral complexities associated with AI in education and emphasizes the importance of aligning ethical beliefs with technological advancements to uphold academic integrity.